Canine mesenchymal stem cell-derived exosomes attenuate renal ischemia-reperfusion injury through miR-146a-regulated macrophage polarization - Liu, HaiFeng; Deng, Hongchuan; Huang, Haocheng; Cao, Jiahui; Wang, Xinmiao; Zhou, Ziyao; Zhong, Zhijun; Chen, Dechun; Peng, Guangneng (Frontiers in Veterinary Science, 2024)
IntroductionThe most common factor leading to renal failure or death is renal IR (ischemia-reperfusion). Studies have shown that mesenchymal stem cells (MSCs) and their exosomes have potential therapeutic effects for IR injury by inhibiting M1 macrophage polarization and inflammation. In this study, the protective effect and anti-inflammatory mechanism of adipose-derived mesenchymal stem cell-derived exosomes (ADMSC-Exos) after renal IR were investigated.MethodInitially, ADMSC-Exos were intravenously injected into IR experimental beagles, and the subsequent assessment focused on inflammatory damage and macrophage phenotype. Furthermore, an in vitro inflammatory model was established by inducing DH82 cells with LPS. The impact on inflammation and macrophage phenotype was then evaluated using ADMSC and regulatory miR-146a.ResultsFollowing the administration of ADMSC-Exos in IR canines, a shift from M1 to M2 macrophage polarization was observed. Similarly, in vitro experiments demonstrated that ADMSC-Exos enhanced the transformation of LPS-induced macrophages from M1 to M2 type. Notably, the promotion of macrophage polarization by ADMSC-Exos was found to be attenuated upon the inhibition of miR-146a in ADMSC-Exos.ConclusionThese findings suggest that miR-146a plays a significant role in facilitating the transition of LPS-induced macrophages from M1 to M2 phenotype. As a result, the modulation of macrophage polarization by ADMSC-Exos is achieved via the encapsulation and conveyance of miR-146a, leading to diminished infiltration of inflammatory cells in renal tissue and mitigation of the inflammatory reaction following canine renal IR.